Workplace Well-Being Among Hospital Nurses: Perspectives of Indonesian Staff Nurses - Achmad Fathi; Hanny Handiyani; Tuti Afriani; Dwi Tyastuti (Caring: Indonesian Journal of Nursing Science, 2025)
Well-being is a unique phenomenon perceived by nurses. Nurses have their own definition of well-being based on their work experience. This study aimed to examine the nurses’ workplace well-being from the perspective of Indonesian staff nurses within hospital settings. A qualitative interpretive descriptive design was employed in this study. Participants were recruited from a university hospital in Medan, Indonesia, comprising 10 staff nurses representing the emergency department, intensive care unit, and inpatient wards. Data were collected through a focus group discussion and analyzed using thematic analysis. Data analysis identified three overarching themes that encapsulate staff nurses perspectives on workplace well-being: the ideal concept of nurses workplace well-being, contributing factors to nurses’ workplace well-being, and nurses expectations of hospital administrators to enhance nurses workplace well-being.  Staff nurses hold distinct expectations regarding their workplace well-being, which are shaped by personal and professional factors. Several contributing elements influence their experiences, including organizational support, workload, and interpersonal relationships. The findings indicate that Indonesian staff nurses perceive workplace well-being as a multifaceted and challenging issue. They highlighted their hopes and expectations concerning workplace well-being across psychological, physical, financial, inter-professional relationship, and hospital facilities dimensions. It is imperative that nurse managers and hospital administrators give careful consideration to these concerns and implement evidence-based, targeted strategies to mitigate the challenges that adversely affect nurses’ well-being. Keyword: Hospitals, Nursing Staff, Well-being, Workplace